Book Reviews of China in Xi Jinping Era - Belk, Russell; Pant, Dipak Raj (Journal of Leadership, Accountability and Ethics, 2022)
Recently, Dr. Shu Xiaohui, a professor at the Business School of Huaihua University in China, and his colleagues published a new book entitled China in Xi Jinping Era. It is an informative volume about major policy guidelines from China's leadership with Mr. Xi Jinping at the core. This volume is part of an Englishlanguage publication series (Modern China Series) that started releasing books on China's socio-economic development has been published by North America Business Press since 2011. The co-authors of this volume have tried to explain some key-respects economic policy, environmental and land-use policy, tourism in rural areas, consumption patterns and lifestyle, internet technology and social media in China's current development process.